A Comprehensive Study of the Interaction between Peptidoglycan Fragments and the Extracellular Domain of Mycobacterium tuberculosis Ser/Thr Kinase PknB. (14th September 2017) - Wang, Qianqian; Marchetti, Roberta; Prisic, Sladjana; Ishii, Kentaro; Arai, Yohei; Ohta, Ippei; Inuki, Shinsuke; Uchiyama, Susumu; Silipo, Alba; Molinaro, Antonio; Husson, Robert N.; Fukase, Koichi; et al.
Abstract: The Mycobacterium tuberculosis Ser/Thr kinase PknB is implicated in the regulation of bacterial cell growth and cell division. The intracellular kinase function of PknB is thought to be triggered by peptidoglycan (PGN) fragments that are recognized by the extracytoplasmic domain of PknB. The PGN in the cell wall of M. tuberculosis has several unusual modifications, including the presence of N ‐glycolyl groups (in addition to N ‐acetyl groups) in the muramic acid residues and amidation ofd ‐Glu in the peptide chains. Using synthetic PGN fragments incorporating these diverse PGN structures, we analyzed their binding characters through biolayer interferometry (BLI), NMR spectroscopy, and native mass spectrometry (nMS) techniques. The results of BLI showed that muropeptides containing 1, 6‐anhydro‐MurNAc and longer glycan chains exhibited higher binding potency and that the fourth amino acid of the peptide stem, d ‐Ala, was crucial for protein recognition. Saturation transfer difference (STD) NMR spectroscopy indicated the major involvement of the stem peptide region in the PASTA‐PGN fragment binding. nMS suggested that the binding stoichiometry was 1:1. The data provide the first molecular basis for the specific interaction of PGN with PknB and firmly establish PGNs as the effective ligands of PknB. Abstract : Within bounds : Bacterial muropeptides containing 1, 6‐anhydro‐MurNAc exhibit higher binding potency than regular N ‐acetylmuramic acid (MurNAc) with ED‐PknB from M. tuberculosis . The binding was analyzed with biolayer interferometry, STD NMR spectroscopy, and native mass spectrometry. This work provides insight into the molecular basis of binding of peptidoglycan fragments to the PASTA domains of PknB.